Uniformly distributed ridge approximation of some classes of harmonic functions - Babenko, V. F.; Levchenko, D. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We determine the exact values of the uniformly distributed ridge approximation of some classes of harmonic functions of two variables.